Fire resistance of circular steel tubes infilled with ultra-high strength concrete with external fire protection - Lyu, Xiao (Array, 2019)
In this paper, a non-linear three-dimensional finite element model is presented in order to study the behaviour of axially loaded ultra-high strength concrete filled circular hollow tubular columns exposed to fire. Ultra-high strength concrete with compressive strength greater than 180 N/mm2 has been developed for concrete filled tubes for use in high–rise buildings. This paper studies the structural performance of fire protected ultra-high strength concrete filled tubular columns exposed to the standard ISO fire. The aim of this work is to understand and represent the behaviour of axially loaded ultra-high strength concrete filled circular hollow tubular columns in fire situations and to compare calculation results with experiment. The numerical analyses are carried out using a general finite element analysis package ABAQUS and the results are validated against the test results in terms of heat distribution and mechanical behavior. Comparison with the test results showed a reasonable agreement with finite element results in terms of temperature prediction and load displacement behavior during the fire.